2008
DOI: 10.1523/jneurosci.2557-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Oxoguanine Glycosylase 1 Protects Against Methamphetamine-Enhanced Fetal Brain Oxidative DNA Damage and Neurodevelopmental Deficits

Abstract: In utero methamphetamine (METH) exposure enhances the oxidative DNA lesion 7,8-dihydro-8-oxoguanine (8-oxoG) in CD-1 fetal mouse brain, and causes long-term postnatal motor coordination deficits. Herein we used oxoguanine glycosylase 1 (ogg1) knock-out mice to determine the pathogenic roles of 8-oxoG and OGG1, which repairs 8-oxoG, in METH-initiated neurodevelopmental anomalies. Administration of METH (20 or 40 mg/kg) on gestational day 17 to pregnant ϩ/Ϫ OGG1-deficient females caused a drug dose-and gene dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 49 publications
5
56
0
Order By: Relevance
“…A previous report supported an OGG1-independent accessory role for CSB in 8- (34). Thus, the less dramatic increases in 8-oxoG observed in this study of Csb m=m mice, compared with our previous studies in CD-1 and Ogg1 À=À mice (22,52), may be accounted for by the substantially higher intrinsic OGG1-dependent 8-oxoG repair activity in the Csb strain, together with the secondary independent role that CSB plays in 8-oxoG repair. The enhanced susceptibility to oxidative DNA damage in METH-exposed fetal brains from Csb m=m mice was not observed in fetal liver, and may reflect tissue-specific differences in CSB function, ROS formation and=or activity of antioxidative enzymes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A previous report supported an OGG1-independent accessory role for CSB in 8- (34). Thus, the less dramatic increases in 8-oxoG observed in this study of Csb m=m mice, compared with our previous studies in CD-1 and Ogg1 À=À mice (22,52), may be accounted for by the substantially higher intrinsic OGG1-dependent 8-oxoG repair activity in the Csb strain, together with the secondary independent role that CSB plays in 8-oxoG repair. The enhanced susceptibility to oxidative DNA damage in METH-exposed fetal brains from Csb m=m mice was not observed in fetal liver, and may reflect tissue-specific differences in CSB function, ROS formation and=or activity of antioxidative enzymes.…”
Section: Discussionsupporting
confidence: 77%
“…The increase in oxidative DNA damage, as well as susceptibility to postnatal motor coordination deficits, in CSBdeficient offspring exposed to METH compared to wild-type littermates was not as dramatic as in CD-1 outbred mice and Ogg1 knockout mice (22,52). To investigate the mechanism responsible for the relative resistance of the Csb þ=þ mice to METH-initiated 8-oxoG formation and subsequent postnatal motor coordination deficits, we compared 8-oxoG repair capacity in the fetal brain of the Csb þ=þ mice to that in the more sensitive CD-1 strain.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…80,81 In the present study, it was observed that aging increases the levels of 8-oxoG in hippocampus of rats, which potentially could jeopardize brain function. 82,83 Indeed, the repair of 8-oxoG is a high priority of cells for survival. The total protein content of OGG1 was increased in aged rats, which could be a cellular attempt to combat the enhanced levels of 8-oxoG, but, in this case, without significant success.…”
mentioning
confidence: 99%
“…The mutagenic role of 8-oxo-dG in cancer is generally appreciated, but this oxidative macromolecular lesion also may affect gene transcription, resulting in neurodegeneration. For example, we recently found that postnatal neurodevelopmental deficits caused by in utero exposure to METH are enhanced in knockout mice deficient in oxoguanine glycosylase 1 (OGG1), the major enzyme for repairing 8-oxo-dG (32). A similar process may occur in adults exposed to MDMA since METH also is bioactivated by PHSs (30).…”
Section: Discussionmentioning
confidence: 99%